Exploring thermal and entropic behaviors in nanofluid stagnation point flow with nonlinear dynamics - M.A. Shahzad; M.S. Anwar; A. Abbas; Taseer Muhammad; Refka Ghodhbani; V. Puneeth (Case Studies in Thermal Engineering)
This study investigates the optimization of heat and mass transfer in nanofluid stagnation point flow by analyzing entropy generation and its underlying physical mechanisms. Nanofluid technology, widely applied in thermal energy storage, and heat exchangers represents a significant advancement in modern thermal systems. While nanofluids enhance heat transfer rates, optimizing thermal conductivity through nanoparticle dispersion remains a key challenge. This work also incorporates the effects of a nonlinear chemical reaction to evaluate its impact on coupled heat and mass transport. The governing nonlinear partial differential equations, including momentum, energy, and concentration expressions, are reduced to a system of coupled ordinary differential equations using local similarity transformations. These equations are solved numerically using a Runge–Kutta scheme in MATLAB. The results, presented through tables and graphs, demonstrate how velocity, temperature, and concentration profiles vary with key physical parameters. Entropy generation is shown to increase with higher porosity, while reductions in slip and Williamson fluid parameters decrease it. Furthermore, the skin friction coefficient increases by approximately 7 % when the magnetic parameter M increases from 0 to 0.5, whereas the Nusselt number decreases by nearly 28.6 % as M increases from 0 to 1. Additionally, the local Sherwood number decreases by approximately 16.7 % when the permeability parameter Kp increases from 0 to 0.3. These findings provide practical insights into enhancing nanofluid based heat and mass transfer systems for engineering applications.